Michael Addition Reaction of Some 3,3-Dimethyl-2,6-diarylpiperidin-4-ones - Gopalakrishnan, M.; Baskar, G.; Winfred Jebaraj, J. (Asian Journal of Chemistry, 2010)
In this paper, Michael addition reaction is carried out by treating 3,3-dimethyl-2,6-diarylpiperidin-4-ones (1a-c) with methyl vinyl ketone in the presence of sodium ethoxide. The products 2a-c and 3a-c formed are analyzed by UV, IR, 1H NMR and 13C NMR spectral methods. In all the cases, the 1H NMR studies confirm the trans- ring fusion.